2020
DOI: 10.4212/cjhp.v73i3.2997
|View full text |Cite
|
Sign up to set email alerts
|

Point Prevalence Survey of Benzodiazepine and Sedative-Hypnotic Drug Use in Hospitalized Adult Patients

Abstract: Background: Benzodiazepines and sedative-hypnotic drugs (BZD/ SHDs), such as zopiclone and the antidepressant trazodone, pose risks such as falls, fractures, and confusion, especially for older adults. Use of these drugs in the acute care setting is poorly understood.Objectives: To determine the point prevalence and characteristics of use of BZD/SHDs in hospitals in Nova Scotia, Canada.Methods: A point prevalence survey was conducted for adults admitted to all hospitals with at least 30 acute care beds between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…One may be concerned that BZRA deprescribing would just reflect a switch to another sedative medication, such as trazodone or mirtazapine [ 48 , 49 ]. Indeed, psychotropic polypharmacy was already high in our population [ 6 ] and is also a subject of concern in older people [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…One may be concerned that BZRA deprescribing would just reflect a switch to another sedative medication, such as trazodone or mirtazapine [ 48 , 49 ]. Indeed, psychotropic polypharmacy was already high in our population [ 6 ] and is also a subject of concern in older people [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials 7 11 and reviews 12 or meta-analyses 13 have reported trazodone’s general safety and subjective efficacy when used for primary and secondary insomnia. Furthermore, trazodone has been reported to be among the most widely prescribed sleep aids in the United States 12 and in Nova Scotia, Canada 14 . However, trazodone is not approved by U.S. Food and Drug Administration (FDA) for sleep disorders 3 , and the American Academy of Sleep Medicine Clinical Practice Guideline 2 did not suggest that clinicians used trazodone as a treatment for sleep onset or sleep maintenance in adults because the evidence for its use for those purposes was limited.…”
Section: Introductionmentioning
confidence: 99%
“…Participants in the control group will be given standard treatment based on BBT-I combined with oral trazodone medication (25–150 mg trazodone as an adjuvant therapy, 30 minutes before going to bed). Trazodone is selected because it is one of the most common drug prescriptions for insomnia in clinical practice [57–60] . If the patient refuses to take trazodone, we will provide BBT-I only and record it.…”
Section: Methodsmentioning
confidence: 99%